Evaluation of treatment response for breast cancer: are we entering the era of “biological complete remission”? - Bian, Li; Wang, Tao; Liu, Yi; Zhang, Hui-Qiang; Song, Jin-Jie; Zhang, Shao-Hua; Wu, Shi-Kai; Song, San-Tai; Jiang, Ze-Fei (Chinese Journal of Cancer Research; Vol 24, No 4 (December 07, 2012): Chinese Journal of Cancer Research, 2012)
Breast cancer is one of the most common malignancies in women. The post-operative recurrence and metastasis are the leading causes of breast cancer-related mortality. In this study, we tried to explore the role of circulating tumor cell (CTC) detection combination PET/CT technology evaluating the prognosis and treatment response of patients with breast cancer; meanwhile, we attempted to assess the concept of “biological complete remission” (bCR) in this regard. A 56-year-old patient with breast cancer (T2N1M1, stage IV left breast cancer, with metastasis to axillary lymph nodes and lungs) received 6 cycles of salvage treatment with albumin-bound paclitaxel plus capecitabine and trastuzumab. Then, she underwent CTC detection and PET/CT for efficacy evaluation. CTC detection combination PET/CT is useful for the evaluation of the biological efficacy of therapies for breast cancer. The bCR of the patient appeared earlier than the conventional clinical imaging complete remission and promised the histological (pathological) complete remission. The integrated application of the concepts including bCR, imageological CR, and histological CR can achieve the early and accurate assessment of biological therapeutic reponse and prognosis of breast cancer.